VD_FINDINFO HC / 2017 / 240 vom 1. März 2017 - VD Tribunal cantonal (2017)
LIQUIDATION DU RÉGIME MATRIMONIAL, DÉCISION DE RENVOI, TRIBUNAL FÉDÉRAL | 650 al. 1 CC, 651 al. 1 CC, 308 al. 1 let. a CPC (CH), 334 CPC (CH)